Relationship between knowledge of acute respiratory tract infection and use of face masks in motorcyle online drivers - Ahmad Saepudin; Eveline Margo (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: Data in 2013 states that the prevalence of acute respiratory infections (ARI) is 25%. One of the factors that cause ISPA is air pollution. This factor is one of the risk factors for motorcycle taxi drivers who are always exposed to air pollution. Knowledge of ARI that is sufficient to influence the use of masks can help prevent ARI from occurring.Objective: This study aims to determine the relationship between knowledge of ARI and the behaviour of using masks among online motorcycle drivers.Methods: This study was an analytical observational with a cross-sectional design attended by 139 online motor cycle drivers around Grogol, Petamburan, West Jakarta, from July to December 2017. Data collection was done by filling out a questionnaire that includes demographic data, the use of masks, and knowledge of ARI. Data analysis used Fisher's test with significance level p<0,05.Results: A total of 139 respondents were collected, consisting of 131 (94.2%) men and 8 (5.8%) women. The average age of > 30 years old is 77 (55.4%) people. Most respondents' education level was SMA/SMK/SLTA as many as 111 (79.9%) people. From the results of Fisher's test, it was found that the probability value p=0.362 was greater than the significance value (0.05).Conclusion: There is no significant relationship between the level of knowledge about ARI and the use of masks among online motorcycle drivers.